2014
DOI: 10.15255/cabeq.2013.1888
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation and Performance Studies of an Alginate Degrading and Ethanol Producing Strain

Abstract: Bioethanol production from brown algae is a promising way to help solve the energy problem. Alginate is a major component of brown algae, but it cannot be utilized for ethanol fermentation. In order to improve the utilization rate of algae, high alginate fermentation strains should be obtained. In this research, alginate fermentations were carried out and 6 alginate degrading strains were obtained from different samples. The ethanol yield of strain 5 was the highest, which was 0.154 g g -1 (ethanol to alginate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In the fermentation process, cells grow first, and then release extracellular enzyme to realize the utilization of alginate. Therefore, the soluble sugar generated by pretreatment is beneficial to the cell growth and can significantly improve the yield of ethanol [ 27 ]. This point can also be confirmed by the measurement of soluble sugar.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fermentation process, cells grow first, and then release extracellular enzyme to realize the utilization of alginate. Therefore, the soluble sugar generated by pretreatment is beneficial to the cell growth and can significantly improve the yield of ethanol [ 27 ]. This point can also be confirmed by the measurement of soluble sugar.…”
Section: Resultsmentioning
confidence: 99%
“…The pH value is also an important factor affecting the fermentation process of ethanol. Acid conditions are more suitable for yeast fermentation [ 27 ]. The activity of the microbial enzyme has a constant pH adaptation range.…”
Section: Resultsmentioning
confidence: 99%
“…Some strains can also utilize dextran, glucose and mannitol to produce ethanol, which are released from brown algae after pretreatment with acids or enzymes (Adams et al 2009; Lee and Lee 2012). Zhang et al (2014) reported a strain that can directly utilize alginate to produce ethanol. To date, only a few wild strains have been reported to simultaneously utilize the main components of brown algae, including alginate, mannitol, laminarin, fucose and glucose, as carbon sources to produce ethanol (Ji et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the utilization rate of algae, high alginate fermentation strains should be obtained not only from gene engineering technology but also from natural isolation. In our previous research 21 , alginate degrading strains were isolated from different samples with alginate as the only carbon source and several strains that showed ethanol fermentation ability were obtained through TTC selection experiments and fermentation experiments. The ethanol yield of strain 5 was the highest, which was 0.154 g g -1 (ethanol to alginate).…”
Section: Introductionmentioning
confidence: 99%